Analysis of Common Cause Failure in the Safety Calculation for Railway Signaling System - TAN Shaobo; TANG Ganglin; HUANG Aiping (Kongzhi Yu Xinxi Jishu)
CCF (common cause failure) analysis is not widely applied in current safety calculation, and this will lead to an over optimistic assessment of safety and result in potential safety hazards. This paper presented a CCF analysis method which takes the AND gates of FTA (failure tree analysis) as its analysis object and combines the β-factor method and the independent analysis method. No complex CCF model needs to be built and analyzing and computing process is simplified. An example of a typical 2 out of 2 AND redundancy design was given to prove that the method can further improve the safety assessment results and has good applicability and maneuverability.